The impact of seizures on pregnancy and delivery. (May 2015) - Sveberg, Line; Svalheim, Sigrid; Taubøll, Erik
Highlights: Limited knowledge on the impact of seizures in pregnancy and delivery. Seizures may affect the foetal heart during pregnancy and delivery. Seizures in pregnancy may possibly affect the size and cognition of the child. Epilepsy is not in itself an indication for caesarean delivery. Status epilepticus is rare during pregnancy and delivery. Abstract: Purpose and methods: The treatment of women with epilepsy during pregnancy is known to increase the risk of teratogenic effects. Whether seizures during pregnancy have a deleterious effect on the developing child is difficult to determine, but recent animal studies, case studies, cohort studies and population studies have provided useful insights. Results and conclusion: Seizures before pregnancy are a predictor for seizures during pregnancy, and catamenial epilepsy may also predict the course of seizures during pregnancy. A first epileptic seizure may also have implications for the pregnancy, depending on the seizure aetiology. Seizures affecting maternal awareness and responsiveness may have cardiac effects on the foetus and may impact on the weight of the newborn. Status epilepticus in pregnancy is rare, but isolated cases of perinatal death and malformations after status epilepticus have been reported in women on antiepileptic drugs. Seizures during delivery occur in about 2% of pregnancies of women with epilepsy, and case studies indicate that the foetal heart may be affected. However, a diagnosis of epilepsy is not an indication per se for caesarean delivery. A well-planned pregnancy can reduce the likelihood of seizures occurring.